Millennial Fiqh: Bridging Islamic Tradition and Social Media in Madrasahs - Nasution, Suryadi; Pohan, Ali Jusri; Khairurrijal; Hayati, Nelmi; Hsb, Zuhdi; Nst, Andri Muda (LETIGES, 2025)
This study examines the implementation of millennial fiqh in madrasahs in Mandailing Natal, Indonesia, to bridge Islamic tradition and digital modernity for Generation Z. Adopting a qualitative case study design, data were collected from three accredited madrasahs (A, B, and C) through in-depth interviews with principals, fiqh teachers, and students, participatory observations in classrooms and digital environments, and analysis of curriculum documents and teaching materials. Data validity was ensured through triangulation of sources (comparing perspectives of teachers, students, and documents), methods (integrating interviews, observations, and document analysis), and theories (referencing maqashid sharia and digital education frameworks). Thematic analysis, based on Miles and Huberman’s model, identified patterns of challenges and opportunities. Findings indicate that millennial fiqh implementation is hindered by normative curricula focused on classical fiqh, limited teacher capacity in digital issues, inadequate technological infrastructure, dominant traditional values, and negative social media influences, such as hate speech and cyberbullying. However, significant opportunities arise from students’ enthusiasm for contemporary fiqh, teachers’ openness to innovation, and technology’s potential as an interactive learning medium. The proposed millennial fiqh curriculum model integrates maqashid sharia principles into social media ethics, contemporary fatwas on digital transactions, and real-world case studies. This model enhances students’ digital ethics awareness, teachers’ pedagogical skills, and madrasahs’ adaptability. Theoretically, millennial fiqh enriches contemporary Islamic education, supporting Sustainable Development Goals for inclusive education with substantial local and global implications.